THE EFFECT OF REPETITION EXERCISE METHOD AND INTENSIVE INTERVAL EXERCISE METHOD ON THE STUDENTS 100 METER SPRINTING ABILITY AT SMP N 1 PARIAMAN - Firdaus, Kamal (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
This research was derived from the problems indicating that the students had lack of capability in 100 meter sprinting. This could be seen from the result of local sport competition held annually. This research sought to explain the improvement of the students 100 meter sprinting ability by using Repetition Exercise Method and Intensive Interval Method. The subject of the research was 22 students at SMP N 1 Pariaman. They were chosen based on their ability in 100 meter sprinting which was lower compared to those from other schools.This was an experimental research which applied quantitative approach. The research was conducted in 16 meetings from May to June 2014. The data gathered were in the form of quantitative data. They were obtained through 100 meter sprinting test. The results of data analysis revealed that: (1) the value of tcalculated gotten by applying Repetition Exercise Method was higher (12.14) than that of ttable (1.812) indicating that the use of that method significantly exerted an influence upon the students 100 meter sprinting ability at SMPNegeri 1 Pariaman, (2) the value of tcalculated gotten by applying Intensive Interval Method was higher (3.27) than that of ttable (1.812) indicating that the use of that method significantly exerted an influence upon the students 100 meter sprinting ability at SMP Negeri 1 Pariaman, and (3) there was no significant different between the use of Repetition Exercise Method and Intensive Interval Method at SMP Negeri 1 Pariaman in which the value of tcalculated (0.28) was higher than ttable (1.860).